Analiza porównawcza japońskich biur informacji kredytowej z polskimi biurami informacji gospodarczej - Telec, Zbigniew (Comparative analysis of Japanese credit information offices with Polish economic information offices, 2006)
The paper presents a comparative analysis of Japanese credit information offices with Polish economic information offices. The analysis lakes legal, cultural as well as economic aspects of both countries into consideration. The article shows a tool used in Poland and in Japan to fight against dishonest dclotors.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1132, s. 246-254